Smartphone Application for Celiac Patients: Assessing Its Effect on Gastrointestinal Symptoms in a Randomized Controlled Clinical Trial - Zeinab Nikniaz; Zahra Akbari Namvar; Masood Shirmohammadi; Elham Maserat (International Journal of Telemedicine and Applications)
Introduction. Considering the lack of inclusive Persian application for celiac patients that covers all aspects of the GFD, we developed a Persian-language application for patients with CD and assessed the effectiveness of a three-month educational intervention delivered via smartphone application compared with standard care on gastrointestinal symptom rating scale (GSRS) score in patients with celiac disease. Methods. In the present parallel randomized controlled clinical trial, 60 patients with CD were assigned randomly to receive education through a smartphone application (n=30) or conventional clinical education (n=30). The patients were asked to use it for getting the required information for three months. We assessed the gastrointestinal symptoms using the gastrointestinal symptom rating scale (GSRS) questionnaire at baseline and three months after interventions. The GSRS total score, celiac disease GSRS (CD-GSRS) score, abdominal pain, reflux, diarrhea, constipation, and indigestion scores were calculated. Results. Out of 60 randomized patients, 58 patients completed the study. In comparison to baseline, the mean score of CD-GSRS score (p=0.001), and indigestion subscore (p<0.001) were significantly decreased in the intervention group. The results of the between-group comparisons showed that there was a significant difference between the two groups only in the mean score of indigestion (p=0.002). Conclusion. According to the results, using a smartphone application for providing information to patients with celiac disease had a significant positive effect on indigestion symptoms compared with routine clinic education. Trial Registration. This trial is registered with the Iranian registry of clinical trials (IRCT code: IRCT20170117032004N2; trial registry date: 2019.6.26).